The geographer Al-Edrisi - his effects on Orientalists: analytical study (Damascus University Journal of arts and humanities sciences, 2023)
The Orientalism movement flourished among Europeans since 1779 AD. It is interested in studying the conditions of Eastern peoples, languages, civilization, history and deeds in all fields of researches, and investigation and translation to show their scientific path. It increased by holding conferences, and the first was Paris in (1873) to discuss studies About the Orient, its religions and civilization, in addition to construction Orientalism institutions in East cities, such as the French Institute in Cairo and Damascus.In this research, it was shown the achievements of the geographer Al-Edrisi, and its roles in European Orientalists researches and their dedications in his personality, biography, his work and what he added to the European Geography, by using Scientific methodologies, such as historical, inductive-deductive, descriptive-analytical, were used to reach the results of the research. These were represented by orientalists, with different scientific specialities and administrative positions. They researched the various effects of al-Idrisi,but the most common and published in the manuscript "Nuzhat al-Mushtaq", and the number of orientalists who were interested in his biography and researches was About fifty, they were from (12) different European countries , the first ones were Germany, France and Italy
Keywords: Orientalism; Manuscript; Orientalist; Idrisi